Alfaiataria double face - Belussi, Wagner Risello (2015)
This work deals with a study about the development of garments of tailoring under a new design angle. It establishes the construction of parts from the double face technique – expression used for objects or products which may be seen or used on both sides. To this end, is based on a review of literature that will be presented the history and some principles about tailoring techniques applied in the manufacturing of garments. Will also be addressed the fundamentals and the particularities of the double face on materialization of products, particularly in the area of fashion. The investigation has focused on a qualitative approach, about a group of people of the male gender with habits in consumption of clothes produced tailored. During the process of creating the collection they were made experimental studies to indentify guidelines to orient the choice of raw materials, textile and sewing and sewing and modelig procedures best suited to propitiate trim and wear ability in parts to be developed. In this sense, the still experimental studies will aim to add more values to the functional and aesthetic aspects of garments from the collection proposal so that differentiate in respect of tailoring products existing in the market.